PO:35:222 | Distinctive Features of Localized Vasculitis of the Gastrointestinal Tract Compared to Takayasu Arteritis: Insights from a Multicenter Cohort Study: Vittorio Dibenedetto1|2|3, Alessandro Tomelleri1|2, Corrado Campochiaro1|2, Elena Baldissera1|2, Luca Moroni1|2, Padoan Roberto4, Marco Matucci-Cerinic1|2|3, Lorenzo Dagna1|2|3 | 1Unit of Immunology, Rheumatology, Allergy and Rare Diseases UNIRAR, IRCCS San Raffaele Hospital Milan, Italy; 2Inflammation, Fibrosis and Ageing Intitiative INFLAGE, IRCCS San Raffaele Hospital Milan, Italy; 3Vita-Salute San Raffaele University, Milan, Italy Milan, Italy; 4University Hospital of Padova, Department of Internal Medicine and Rheumatology Padova, Italy - di Reumatologia, Società Italiana (Reumatismo, 2026)
Objective. Vascular districts of the gastrointestinal (GI) tract can be affected by arteritic inflammation. This occurs in systemic diseases such as Takayasu arteritis (TAK), or as an isolated manifestation. The latter defines a rare, poorly described condition, known as localized vasculitis of the gastrointestinal tract (LVGT). Despite its distinct presentation, LVGT remains poorly characterized, with limited knowledge of its presentation, imaging and outcomes. Differentiating LVGT from systemic vasculitis is a diagnostic challenge that warrants further investigation. This study aimed to analyze the presenting features and clinical outcomes of a multicentric cohort of patients with LVGT, highlighting key differences from TAK patients and isolated GI vessels’ involvement. MATERIAL ANDMethods. Patients with LVGT were identified from two referral centres. They were required to have at least one comprehensive vascular imaging study demonstrating isolated inflammation in at least one GI artery, with or without involvement of the abdominal aorta. Data were anonymously collected using a standardized case report form, capturing baseline demographic, clinical, biological, radiological findings, treatment, and follow-up outcomes. A comparison of baseline features with a cohort of patients with TAK (classified according to the 2022 Criteria) with involvement of GI arteries from one of the two centers was performed. Non-parametric tests were used.Results. Twelve patients with LVGT were identified (67% male) with a median age at disease onset of 55 years (IQR, 44–62). Diagnostic delay from first symptom onset was 1 month (IQR, 1–4). All patients presented to the Emergency Department. Main presenting symptoms and organ involvement at presentation are summarized in Table. Vasculitis diagnosis was confirmed by a computed tomography angiography (CTA) in all cases. A second imaging evaluation was performed in almost all cases. No patient underwent histological confirmation. Table summarizes the affected vessels. Two patients underwent surgery/intravascular procedure at baseline; one had surgery 8 months later. Glucocorticoids (GC) were started in 11 patients and stopped in 9 after a median of 9 months (IQR, 4–12). Four patients were started on methotrexate. No patient was started on bDMARD. No major complications or deaths were reported during a median observation period of 33 months (IQR, 7–88). Compared to TAK patients, LVGT cases showed significant differences in sex distribution, age at onset, diagnostic delay, vessel involvement and initial GC dosage. Of note, GI symptoms, ischemia, vascular occlusion, and dissection were more frequent in LVGT, while TAK had a longer diagnostic delay.Conclusions. LVGT exhibits unique clinical and demographic characteristics when compared to TAK. Imaging techniques, especially CTA, play a key role in diagnosis. GCs are the primary treatment and show good efficacy with a generally favourable prognosis. Our findings highlight the importance of identifying LVGT as a distinct condition to ensure prompt diagnosis and personalized treatment.